FLT3 is associated with dendritic cell infiltration, tertiary lymphoid structure construction, and predict response to checkpoint inhibitors immunotherapy in solid cancers - Yongchang Tang; Hong Wang; Jiankun Zhang; Chunhui Yang; Fei Xu; Yan Song; Tianen Li; Qiangbo Zhang (Scientific Reports)
Abstract The crosstalk between cancers and the immune microenvironment plays a critical role in malignant progression. FMS-like tyrosine kinase 3 (FLT3) is a frequently mutated gene in acute myeloid leukemia (AML). However, its role in solid cancers remains poorly understood. We analyzed the frequency of FLT3 alterations, its mRNA expression levels, and its prognostic implications across multiple cancer types. Additionally, we explored genes co-expressed with FLT3 and performed gene ontology analysis to identify associated biological processes. We also examined the relationship between FLT3 expression and markers of various immune cells, tertiary lymphoid structures (TLSs), and epithelial-mesenchymal transition. Furthermore, we validated these findings in our own cohort of hepatocellular carcinoma (HCC) patients. We found that FLT3 alteration and expression were both significantly upregulated in AML and were associated with poor prognosis, which is opposite to its role in solid cancers. The genes co-expressed with FLT3 in solid cancers were correlated with the regulation of the immune microenvironment. FLT3 was positively correlated with the formation of TLSs in only solid cancers, which was especially relevant to central memory T cells. We also found that FLT3 was positively correlated with the infiltration of NK cells, B cells, and DCs. It also positively correlated with the occurrence of apoptosis in solid cancers, but exhibited opposite roles in AML. The structural factors of the TLSs were positively correlated with FLT3 in solid cancers, but exhibited a negative correlation in AML. Meanwhile, we further validated the above conclusions in our own HCC cohort and demonstrated that FLT3 could serve as a predictive indicator of PD-1 treatment efficacy in HCC. In summary, the role of FLT3 is different in AML and solid cancers. FLT3 is associated with dendritic cell infiltration, tertiary lymphoid structure construction, and predict response to checkpoint inhibitors immunotherapy in HCC.